Follicular development and reproductive hormone changes during postpartum anestrus in suckled beef cows - R.C. Perry; L.R. Corah; W.E. Beal; G.H. Kiracofe; J. Ernest Minton; R.C. Cochran; J.R. Brethour; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1991)
Twenty-six, Hereford x Angus, suckled cows were utilized to determine patterns of follicular development and associated changes in reproductive hormones during postpartum anestrus and first estrous cycles. Ultrasonography per rectum was used to monitor follicular size and detect ovulation. Dietary energy and(or) body condition influenced patterns of follicular development during postpartum anestrus. Follicular growth occurred in waves during this period in cows that were in adequate body condition and adequately fed, and follicular development appeared to be related to serum concentrations of luteinizing hormone and estradiol. Two distinct characteristics were associated with follicular development before the first postpartum ovulation. First, diameter of dominant follicles increased with successive follicular waves. Second, a large dominant follicle was present for an extended time before development of the first ovulatory follicle and appeared to be involved in the mechanism that initiates the first ovulation after calving.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Cattle; Postpartum; Ovarian follicles; Ultrasonography